The doll in the garden : a ghost story - Hahn, Mary Downing (Boston : Houghton Mifflin, 1989)
After Ashley and Kristi find an antique doll buried in old Miss Cooper's garden, they discover that they can enter a ghostly turn-of-the-century world by going through a hole in the hedge.
1 2 9 10 11 12 13 16 18 19 20 21 25 27 31 36 38
Keywords: Space and time -- Fiction; Space and time -- Juvenile fiction; Adventure -- Juvenile fiction